A scientific study on fraud detection in electronic payments using machine learning methods - Shmatko, O. V.; Antypin, I.; Шматко, О. В. (International Scientific Unity, 2025)
Electronic payment systems have transformed financial transactions, offering efficiency and convenience. However, with their increasing adoption, the risks of fraudulent activities have grown. Fraudsters exploit vulnerabilities in digital payment platforms, necessitating the development of sophisticated fraud detection mechanisms. Traditional security measures are often reactive rather than proactive, making them inadequate in preventing real-time financial crimes.